2016
DOI: 10.1080/02786826.2016.1257109
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-based materials for inactivation of aerosolized spores of Bacillus anthracis surrogates

Abstract: Energetic materials generating biocidal combustion products to disable airborne pathogenic microorganisms (including bio-threat agents) were designed as compounds of halogens and metals with high heats of oxidation. Thermally stable Al-based powders containing iodine and chlorine were prepared using ball-milling at room and cryogenic temperatures. Such powders can replace pure aluminum in metallized energetic formulations. Their stability and halogen release were quantified using thermo-gravimetric analysis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
0
14
2
Order By: Relevance
“…Extensive researches have been recently carried out to develop ingredients for explosives and incendiaries, which produce combustion products capable of a drastic reduction of the spore viability at temperatures and on time scales typical for munition-target interactions. The present study builds upon the foundation created by previous efforts of this team (Zhang et al 2012;Grinshpun et al 2010aGrinshpun et al ,b, 2012Grinshpun et al , 2017Zhang et al 2010;Aly et al 2014;Wang et al 2016aWang et al ,b, 2017Abraham et al 2016). To be effective in a typical military application, aerosolized spores should be inactivated by factors of 10 4 or better, above 100 C, and within seconds or less.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Extensive researches have been recently carried out to develop ingredients for explosives and incendiaries, which produce combustion products capable of a drastic reduction of the spore viability at temperatures and on time scales typical for munition-target interactions. The present study builds upon the foundation created by previous efforts of this team (Zhang et al 2012;Grinshpun et al 2010aGrinshpun et al ,b, 2012Grinshpun et al , 2017Zhang et al 2010;Aly et al 2014;Wang et al 2016aWang et al ,b, 2017Abraham et al 2016). To be effective in a typical military application, aerosolized spores should be inactivated by factors of 10 4 or better, above 100 C, and within seconds or less.…”
Section: Introductionmentioning
confidence: 91%
“…Studies have generated substantial data on the spore inactivation by specific treatments, e.g., through exposure to heat and certain chemicals (Mullican et al 1971;Setlow et al 2002;Melly et al 2002;Rice et al 2005;Setlow 2006; Grinshpun et al 2010a;Johansson et al 2011;Adhikari et al 2016;Li et al 2017). Some studies have demonstrated that stressresistant bacterial spores exposed to elevated temperatures and products released from combustion of certain compositions can be effectively inactivated even over short exposure time intervals (Aly et al 2014;Wang et al 2015;Abraham et al 2016;Grinshpun et al 2017). A variety of halogens, especially iodine and chlorine, has been explored for inactivation of viable airborne spores (Tennen et al 2000;Burton et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burn times measured for several nanocomposite RM powders prepared by mechanical milling and injected in an air‐acetylene flame are shown in Figure . These RMs contain such additives as I 2 , Cl 2 , or S, expected to generate biocidal combustion products aimed to inactivate biological agents, such as anthrax‐laced powders.…”
Section: Characterization Of Rsmsmentioning
confidence: 99%
“…Burn times as a function of particle sizes for some RM powders containing biocidal additives, I 2 , Cl 2 , or S, burning while being injected in an air‐acetylene flame. Results for pure Al and Mg are shown for reference …”
Section: Characterization Of Rsmsmentioning
confidence: 99%